2018
DOI: 10.1007/s00038-018-1155-x
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, sexual risk taking, and sexual victimization in Ghanaian adolescents and young South African adults

Abstract: Our findings underscore the importance of food access on young people's sexual health, regardless of gender. Prevention efforts may be more relevant when integrated with food security interventions that target vulnerable adolescents and young adults, irrespective of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…The prevalence of FIS has been reported to be 60% among South African women in their postpartum period [38] and 32% among women in Northern Jordon [39]. Another study also found the prevalence of FIS to be 72% among Ghanaian adolescents girls and 83% among young adults in South Africa [40], while a study among rural women in Kenya reported FIS rates of 48% [41]. These prevalence rates are higher than what we observed in our population where the problem of food insecurity was found to be of moderate public health concern (23%).…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of FIS has been reported to be 60% among South African women in their postpartum period [38] and 32% among women in Northern Jordon [39]. Another study also found the prevalence of FIS to be 72% among Ghanaian adolescents girls and 83% among young adults in South Africa [40], while a study among rural women in Kenya reported FIS rates of 48% [41]. These prevalence rates are higher than what we observed in our population where the problem of food insecurity was found to be of moderate public health concern (23%).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, a number of studies conducted in poor countries emphasize that food insecurity produces more dangerous sexual circumstances for women, including inconsistent condom use, abusive relationships, transactional sex, or participation in commercial sex work (e.g. Masa et al 2019 ; Pascoe et al 2015 ; Pellowski et al 2018 ; Tsai et al 2012 ; Tsai and Weiser 2014 ; Weiser et al 2007 ).…”
Section: Food Insecurity Hiv Susceptibility and Risky Sexual Behavimentioning
confidence: 99%
“…FAO 2020 ), and also has important relevance for creating gender-based vulnerabilities to HIV (e.g. Masa et al 2019 ). Prior research identifies several important physiological and social factors that link food insecurity to women’s vulnerability to HIV in less-developed countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside these methodological considerations, the lack of a theoretical perspective focusing on transitions also limited the interpretation of some findings. For instance, Masa et al (2018) brought forward new evidence on the role of food insecurity on sexual risk taking practices using two samples with mean ages of 17 and 22, yet missed the opportunity to discuss differences in keeping with the different life periods associated with these two age groups.…”
mentioning
confidence: 99%